PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE UNTUK MEMPERBAIKI PROSES PEMBELAJARAN DAN MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS V SD NEGERI 21 BALAI MAKAM KECAMATAN MANDAU - Fitri Meiharty (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2018)
This research is motivated by the problem of low student learning outcomes in social studies learning at elemetary school 21Balai Makam, Mandau District. The purpose of this study was to improve the learning process and improve social studieslearning outcomes of fifth grade students of elementary school 21 Balai Makam in the 2015/2016 academic year through theapplication of Think Pair Share cooperative learning models. This research was carried out in two cycles. The subjects of thestudy were 26 grade V students consisting of 14 male students and 12 female students. This research was carried out in the evensemester of 2015/2016 academic year in April 2016. Social studies learning outcomes in cycle 1 were obtained on average 73.26and cycle II with an average of 88.33. It can be concluded that the Cooperative Type Think Pair Share learning model canimprove the social studies learning outcomes of fifth grade students of elementary school 21 Balai Makam.